NUMERICAL SIMULATION OF UNSTEADY VISCOUS FLOW AROUND AIRSHIP USING VORTEX METHOD - Subagyo (Indonesian Journal of Aerospace, 2010)
The grid-less Vortex Method has been developed as the tool for the analysis of two-dimensional (2D) and three-dimensional (3D) complex flows in various engineering applications. In the present study, unsteady flows around a slightly complex geometry (bare hull of an airship and body of an airship) at angles incidence α= 10°, 20°, and 30° were investigated by using the vortex method for a high Reynolds number, Re = 3.9105. The flow-pattern, velocity field, coefficient of pressure distribution on the bare hull and the surface of the airship body, and the aerodynamic coefficient were obtained from numerical calculations. A comparison of the numerical results with the experimental observations showed a good agreement.